2011
DOI: 10.1002/mc.20731
|View full text |Cite
|
Sign up to set email alerts
|

Loss of imprinting and abnormal expression of the insulin‐like growth factor 2 gene in gastric cancer

Abstract: This study examined the frequency of loss of imprinting (LOI) and expression of the insulin-like growth factor 2 (IGF2) gene, and their relationship to selected clinical and pathological factors, in a well defined series of 90 Chinese patients with gastric cancer (GC) and 90 matched patients (controls) diagnosed with nonmalignant conditions. Using peripheral blood and gastric tissue samples, polymerase chain reaction-based assays and restriction endonuclease (Apa I) digestion revealed 33 GC patients and 21 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Although more cases should be analyzed, our data suggest that the IGF2 methylation level in blood leukocyte DNA may be a surrogate marker of the risk for GC. It has been reported that IGF2 LOI was associated with an increased expression of IGF2 level in both tumors and blood of GC cases,18, 32 supporting our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although more cases should be analyzed, our data suggest that the IGF2 methylation level in blood leukocyte DNA may be a surrogate marker of the risk for GC. It has been reported that IGF2 LOI was associated with an increased expression of IGF2 level in both tumors and blood of GC cases,18, 32 supporting our results.…”
Section: Discussionsupporting
confidence: 92%
“…Genomic imprinting is a form of gene silencing that is epigenetic in origin. Loss of imprinting (LOI) of IGF2 was discovered in embryonal tumors of childhood, such as Wilms' tumors, but it is found commonly in many types of cancer, including ovarian, lung, colon17 and gastric18 cancers. In Wilms' tumors, LOI results in increased expression of IGF2, an important autocrine growth factor for many cancers.…”
mentioning
confidence: 99%
“…Some (Heijmans et al, 2008) but not all (Waterland et al, 2010) have found methylation differences at the IGF2 DMR between individuals exposed and not exposed to environmental stimuli such as nutrient challenges, suggesting that this DMR is a reasonable epigenetic biosensor for evaluating early environmental exposures (Hoyo et al, 2009). Deregulation of IGF2 expression has been linked to overgrowth disorders (Morison and Reeve, 1998; Delaval et al, 2006; Riccio et al, 2009), obesity (Roth et al, 2002; Gomes et al, 2005) and cancer (Taniguchi et al, 1995; Sullivan et al, 1999; Ravenel et al, 2001; Cui et al, 2003; Murphy et al, 2006; Xu et al, 2006; Byun et al, 2007; Chao and D'Amore, 2008; Ito et al, 2008; Pollak, 2008; Paradowska et al, 2009; Shetty et al, 2010; Zuo et al, 2011). We (Hoyo et al, 2009) and others (Mathers, 2007; Heijmans et al, 2009) have proposed that methylation shifts at sequences regulating genomic imprinting can serve as archives of the periconceptional and prenatal environment.…”
Section: Discussionmentioning
confidence: 99%
“…This epigenetic modification is faithfully transmitted to nascent DNA molecules during DNA replication and is maintained during somatic cell proliferation. DNA methylation contributes to the induction and maintenance of transcriptional gene silencing, propagating shifts in gene expression that orchestrate long-term susceptibility to several adenocarcinoma including colon [2, 3], ovary [4], prostate [5, 6], stomach [7], and esophagus [8]. Epigenetic mechanisms have also been hypothesized to link birth weight, a proxy for the well-being of the offspring in utero, with some of these cancers in adulthood [915].…”
Section: Introductionmentioning
confidence: 99%